WORKSHOP PENGUATAN PERAN KELUARGA DALAM MENANAMKAN NILAI KESETARAAN GENDER PADA ORGANISASI KEAGAMAAN - Siti Kholifah (Politeknik Negeri Sriwijaya, 2022)
Gender inequality that occurs in society more detrimental to women than men, and emerges some problems such as marginalization, subordination, stereotype, violence, and double burden towards women. The efforts to tackle gender inequality have been carried out by women’s organizations and government regulations. However, these programs have not achieved yet outstanding results, and various problem have emerged that have weakened the issue of gender equality. For this reason, this workshop aims to strengthen and encourage the internalization of gender equality values in the family through religious organizations in Malang. Based on community service activities, the participants realized the importance of internalization gender values not only in the family, but also in the organizations and the society. This situation can be seen in the critical thingking of the participants in analysis the realities that occurs in the domestic and public spheres. In addition, they are commited to inculcating the values of gender equality and justice in their families and communities, where participants also have a role in the religious organizations who participate in. The program evaluation showed that 93.1% of participants find better understanding in term of gender equality values after attending in the workshop.